Development and Characterisation of a Novel NF-κB Reporter Cell Line for Investigation of Neuroinflammation - Marie-Theres Zeuner; Thomas Vallance; Sakthivel Vaiyapuri; Graeme S. Cottrell; Darius Widera (Mediators of Inflammation)
Aberrant activation of the transcription factor NF-κB, as well as uncontrolled inflammation, has been linked to autoimmune diseases, development and progression of cancer, and neurological disorders like Alzheimer’s disease. Reporter cell lines are a valuable state-of-the art tool for comparative analysis of in vitro drug screening. However, a reporter cell line for the investigation of NF-κB-driven neuroinflammation has not been available. Thus, we developed a stable neural NF-κB-reporter cell line to assess the potency of proinflammatory molecules and peptides, as well as anti-inflammatory pharmaceuticals. We used lentivirus to transduce the glioma cell line U251-MG with a tandem NF-κB reporter construct containing GFP and firefly luciferase allowing an assessment of NF-κB activity via fluorescence microscopy, flow cytometry, and luminometry. We observed a robust activation of NF-κB after exposure of the reporter cell line to tumour necrosis factor alpha (TNFα) and amyloid-β peptide [1-42] as well as to LPS derived from Salmonella minnesota and Escherichia coli. Finally, we demonstrate that the U251-NF-κB-GFP-Luc reporter cells can be used for assessing the anti-inflammatory potential of pharmaceutical compounds using Bay11-7082 and IMD0354. In summary, our newly generated cell line is a robust and cost-efficient tool to study pro- and anti-inflammatory potential of drugs and biologics in neural cells.